Exploring the parameter for alternating current electrophoretic deposition of carbon nanotubesconducting polymer : a review / Ahmad Fahmi, Intan Syaffinazzilla Zaine and Dr. Norain Isa - Fahmi, Ahmad; Zaine, Intan Syaffinazzilla; Isa, Norain (2020)
Electrophoretic deposition (EPD) has been gaining interest due to its great versatility in process parameters for carbon nanotubes (CNTs) and nanocomposite film deposition. The main objective of this paper is to study the parameters effecting formation of CNTs-conducting polymer films using alternating current electrophoretic deposition (AC-EPD) technique. Systematic review have been conducted to accomplish the objective of the study. Stable colloidal suspension can be achieved by using aqueous solution, dispersant and chemical treatment. Good film deposition can be achieved during AC-EPD by using peak to peak voltage, frequency, duty cycle, deposition period and waveform with average value of 15V, 1000 Hz, 80%, 10 minutes and asymmetrical rectangular wave respectively. In the meantime, this work reviews about applications of AC-EPD other than films or coatings making industries as well.